Contemporary Challenges in Understanding of the Holy Qur’an and Their Solutions: An Analytical Study - Hafiz Amir Shahzad; Muhammad Hammad Saeed (Journal of Religion and Society, 2025)
The Qur'an is a timeless source of guidance for all generations; however, the challenges related to its understanding have varied across different eras. In the contemporary age, the rise of scientific and intellectual advancements, the growing influence of atheism and secularism, modern issues in translation and interpretation, the proliferation of digital media and artificial intelligence, and the persistence of sectarianism have further complicated the comprehension of the Qur'anic message. This study offers an analytical exploration of these modern challenges and proposes possible solutions in light of the Islamic intellectual tradition and contemporary thought.The research highlights that scientific progress has necessitated a fresh perspective in understanding the meanings of the Qur'an. However, the tendency to incorrectly impose scientific theories onto the Qur'anic text has, at times, led to interpretive problems. Likewise, under the influence of atheistic and secular ideologies, new questions have emerged in the field of Qur'anic interpretation that require robust scholarly responses. Moreover, modern translation and exegetical methods face challenges due to linguistic, contextual, and cultural disparities, calling for the establishment of standardized research and interpretative criteria at an international level. Additionally, while digital tools and artificial intelligence have introduced new opportunities for understanding the Qur'an, their unreliable or careless use can open pathways to misguidance. Therefore, it is essential to define strong scholarly and ethical guidelines for their use. The findings of this study emphasize the need to promote an ijtihād-based approach, integrate scientific and intellectual developments within the framework of Islamic teachings, and formulate sound exegetical principles on the basis of authentic scholarly research. It is equally important to provide the younger generation with an environment that harmonizes traditional Islamic knowledge with contemporary disciplines, enabling them to grasp the Qur'anic message more effectively and convey it responsibly. This study is a scholarly effort to address the contemporary challenges of Qur'anic understanding. It not only contributes to Islamic research and education but also offers valuable guidance in formulating appropriate principles for understanding the Qur'an in the modern age. Keywords: Understanding the Qur’an, Contemporary Challenges, Scientific Discourse, Ijtihād, Modern